2022
DOI: 10.3390/foods11233927
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Functional Performance of Emmer, Spelt and Khorasan in Spontaneously Fermented Sourdough Bread

Abstract: The aim of this study was to test the suitability of three different ancient wheat varieties (emmer, spelt and khorasan) to produce spontaneously fermented sourdough bread and to evaluate the impact on the dough rheological properties, ultrastructure and baking quality. Modern wheat sourdough bread and bakery yeast fermented bread were used as controls. Sourdoughs produced from modern and ancient wheats exerted different effects on dough viscoelastic properties, bread specific volume, texture, firming rate, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…Köse had the highest one ( p < .05). In a study, the ash content of spelt and emmer whole wheat flours were found to be 1.98% and 1.87% (Škrobot et al, 2022), which are higher than the ash content of spelt and emmer whole wheat flours used in the present study. When the protein content of whole wheat flours was compared, the protein content of cv Sivas (old wheat) was the highest (16.0%) (14.8%) while that of spelt was the lowest (13.4%).…”
Section: Resultscontrasting
confidence: 54%
“…Köse had the highest one ( p < .05). In a study, the ash content of spelt and emmer whole wheat flours were found to be 1.98% and 1.87% (Škrobot et al, 2022), which are higher than the ash content of spelt and emmer whole wheat flours used in the present study. When the protein content of whole wheat flours was compared, the protein content of cv Sivas (old wheat) was the highest (16.0%) (14.8%) while that of spelt was the lowest (13.4%).…”
Section: Resultscontrasting
confidence: 54%
“…Panelists were recruited from university students and staff, which is a frequent technique in academic research. At that level of test participants, the total data might be segmented with hierarchical cluster analysis (HCA), but that was not involved in that study [ 80 ].…”
Section: Affective Tests Size Of Consumer Panelsmentioning
confidence: 99%
“…This clearly demonstrates that fermented foods offer more advantages than non-fermented foods [24]; therefore, fermentation technology deserves considerable attention from consumers, companies, and researchers. Since kamut powder is well-used in food materials such as muffins and bread [25], and fermented kamut is also used in wheat dough to make bread in the food industry [26,27], fermenting kamut sprouts may offer different benefits to enhance human health.…”
Section: Introductionmentioning
confidence: 99%